Connecting the Micro to the Macro: An Exploration of Micro-Behaviors of Individuals Who Drive CSR Initiatives at the Macro-Level - Poonamallee, Latha (Front Psychol, 2018)
Grounded on a case study on the formation of an inter-corporate CSR initiative in which four corporations from Chennai, India collaborate, this paper explores the micro-behaviors that individual actors engage in to create CSR solutions later adopted at the macro-organizational level. Based on the findings, the paper (1) identifies five categories of micro-behaviors, namely increasing stakeholder salience by turning attention to the ethical and social responsibilities to specific stakeholder groups, emerging as a self-appointed CSR champion by assuming personal responsibility for action, creating CSR initiative prototypes by leveraging personal skills, garnering support by leveraging personal networks and amassing operational resources by organizational resources; (2) explicates the characteristics of individual approach to CSR that makes it different from, but complementary to organizational approach to CSR.